Demographic and Treatment Patterns for Infections in Ambulatory Settings in the United States, 2006‐2010. (January 2014) - May, Larissa; Mullins, Peter; Pines, Jesse; Wilbur, Lee
Abstract Objectives Many factors may influence choice of care setting for treatment of acute infections. The authors evaluated a national sample of U.S. outpatient clinic and emergency department (ED) visits for three common infections (urinary tract infection [UTI], skin and soft tissue infection [SSTI], and upper respiratory infection [URI]), comparing setting, demographics, and care. Methods This was a retrospective analysis of 2006–2010 data from the National Hospital Ambulatory Care Survey (NHAMCS) and National Ambulatory Care Survey (NAMCS). Patients age ≥ 18 years with primary diagnoses of UTI, URI, and SSTI were the visits of interest. Demographics, tests, and prescriptions were compared, divided by ED versus outpatient setting using bivariate statistics. Results Between 2006 and 2010, there were an estimated 40.9 million ambulatory visits for UTI, 168.3 million visits for URI, and 34.8 million visits for SSTI; 24% of UTI, 11% of URI, and 33% of SSTI visits were seen in EDs. Across all groups, ED patients were more commonly younger and black and had Medicaid or no insurance. ED patients had more blood tests (54% vs. 22% for UTI, 21% vs. 14% for URI, and 25% vs. 20% for SSTI) and imaging studies (31% vs. 9% for UTI, 27% vs. 8% for URI, and 16% vs. 5% for SSTI). Pain medications were more frequently used in the ED; over one‐fifth of UTI and SSTI visits included narcotics. In both settings, greater than 50% of URI visits received antibiotics; more than 40% of UTI ED visits included broad‐spectrum fluoroquinolones. Conclusions Emergency departments treated a considerable proportion of U.S. ambulatory infections from 2006 to 2010. Patient factors, including the presence of acute pain and access to care, appear to influence choice of care setting. Observed antibiotic use in both settings suggests a need for optimizing antibiotic use.